2021
DOI: 10.1093/mnras/stab2853
|View full text |Cite
|
Sign up to set email alerts
|

Vertical settling of pebbles in turbulent circumbinary discs and the in situ formation of circumbinary planets

Abstract: The inner-most regions of circumbinary discs are unstable to a parametric instability whose non-linear evolution is hydrodynamical turbulence. This results in significant particle stirring, impacting on planetary growth processes such as the streaming instability or pebble accretion. In this paper, we present the results of three-dimensional, inviscid global hydrodynamical simulations of circumbinary discs with embedded particles of 1 cm size. Hydrodynamical turbulence develops in the disc, and we examine the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
3
10
0
Order By: Relevance
“…All of the mentioned studies so far have used vertically integrated, locally isothermal models, where the cooling timescale is negligible compared to the orbital period of the gas, ignoring changes to the thermal profile of the disc. Kley et al (2019) introduced a radiatively cooled model for the circumbinary disc with migrating planets and Pierens et al (2020Pierens et al ( , 2021) used a three-dimensional (3D) model with βcooling including dust to study the impact of the turbulent disc on in situ planet growth close to the binary.…”
Section: Introductionmentioning
confidence: 99%
“…All of the mentioned studies so far have used vertically integrated, locally isothermal models, where the cooling timescale is negligible compared to the orbital period of the gas, ignoring changes to the thermal profile of the disc. Kley et al (2019) introduced a radiatively cooled model for the circumbinary disc with migrating planets and Pierens et al (2020Pierens et al ( , 2021) used a three-dimensional (3D) model with βcooling including dust to study the impact of the turbulent disc on in situ planet growth close to the binary.…”
Section: Introductionmentioning
confidence: 99%
“…Growing a massive planetesimal seed in-situ through pebble accretion also appears to be very challenging. The inner disc is prone to a parametric instability that generates hydrodynamical turbulence (Papaloizou 2005;Barker & Ogilvie 2014), the main impact of which is to stir up the pebble layer, resulting in inefficient pebble accretion (Pierens et al 2020(Pierens et al , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Ways to overcome the problems with in situ formation have been explored, including having extremely massive protoplanetary discs (Marzari & Scholl 2000;Martin et al 2013;Meschiari 2014;Rafikov & Silsbee 2015), or if the fragments are reaccreted and form second or later generations of planetesimals (Paardekooper & Leinhardt 2010). More recently, it has been shown that in situ pebble accretion scenarios also suffer from difficulties because a parametric instability can generate hydrodynamical turbulence that stirs up pebbles, rendering pebble accretion onto planetary embryos inefficient (Pierens et al 2020(Pierens et al , 2021.…”
Section: Introductionmentioning
confidence: 99%